Sociologie de l’immigrant : Hiroshi Saito et l’institutionnalisation des études sur les Japonais du Brésil (1940-1960) - Matheus Gato de Jesus; Gustavo Takeshy Taniguti (Brésil(s), 2012)
This article studies the relationship between the trajectory of the sociologist Hiroshi Saito (1919-1983) and his work dedicated to Japanese immigrants in Brazil. It shows that the author was of fundamental importance for the institutionalization of studies in this domain, for the academic and scientific world as much as for Japanese immigrants.